2018
DOI: 10.1002/ece3.3996
|View full text |Cite
|
Sign up to set email alerts
|

The thermal dependency of locomotor performance evolves rapidly within an invasive species

Abstract: Biological invasions can stimulate rapid shifts in organismal performance, via both plasticity and adaptation. We can distinguish between these two proximate mechanisms by rearing offspring from populations under identical conditions and measuring their locomotor abilities in standardized trials. We collected adult cane toads (Rhinella marina) from invasive populations that inhabit regions of Australia with different climatic conditions. We bred those toads and raised their offspring under common‐garden condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 41 publications
1
27
1
Order By: Relevance
“…The invasive range of cane toads in Australia includes highly varied environments; climatic conditions in the range core are similar to those in the native range (Central and South America), but intermediate areas and the invasion front receive much less annual rainfall (2,000-3,000 mm in QLD, 400-1,000 mm in NT and WA) and have higher annual mean temperatures (21-24°C in QLD, 24-27°C in NT and WA;Bureau of Meteorology A.G., 2018). Traits such as locomotor performance at high temperatures also follow this pattern (Kosmala, Brown, Christian, Hudson, & Shine, 2018), but others do not. Furthermore, loci putatively under selection are involved in tolerance of temperature extremes and dehydration .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The invasive range of cane toads in Australia includes highly varied environments; climatic conditions in the range core are similar to those in the native range (Central and South America), but intermediate areas and the invasion front receive much less annual rainfall (2,000-3,000 mm in QLD, 400-1,000 mm in NT and WA) and have higher annual mean temperatures (21-24°C in QLD, 24-27°C in NT and WA;Bureau of Meteorology A.G., 2018). Traits such as locomotor performance at high temperatures also follow this pattern (Kosmala, Brown, Christian, Hudson, & Shine, 2018), but others do not. Furthermore, loci putatively under selection are involved in tolerance of temperature extremes and dehydration .…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, loci putatively under selection are involved in tolerance of temperature extremes and dehydration . Traits such as locomotor performance at high temperatures also follow this pattern (Kosmala, Brown, Christian, Hudson, & Shine, 2018), but others do not. For example, behavioral propensity for exploration increases with distance from the introduction site (Gruber, Brown, Whiting, & Shine, 2017).…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, loci 100 putatively under selection are involved in tolerance of temperature extremes and dehydration 101 (Selechnik et al, 2019). Traits such as locomotor performance at high temperatures also follow 102 this pattern (Kosmala et al, 2018), but others do not. For example, behavioral propensity for 103 exploration increases with distance from the introduction site (Gruber et al, 2017).…”
Section: Introduction 56mentioning
confidence: 99%
“…In a second study Brown et al (2015) examined differences in physiology between the offspring of range front and range core toads and found that while immune and stress responses did not differ, juveniles of range-front populations had more neutrophils in their blood, and were more effective at phagocytosis (i.e., killing bacteria) than rangecore juveniles. Consistent with the penetration of invasive cane toads into thermally severe environments in Australia, the thermal dependency of locomotor ability differs among individuals from dispersive versus sedentary populations and is a heritable trait (Kosmala et al 2017(Kosmala et al , 2018.…”
Section: Ecological Correlates Of Dispersal (1) Emigration and Immentioning
confidence: 91%
“…In B. variegata, Cayuela et al (2018c) showed that spatially structured populations experiencing low-persistence breeding patches displayed lower genetic variation due to higher emigration rates and longer dispersal distances than did populations utilising persistent breeding patches. 2014), high salinity or water temperature (Hopkins & Brodie 2015, Pastenes et al 2017Kosmala et al 2017Kosmala et al , 2018, or high altitude (see below), but few of them have investigated the actual genetic bases of these adaptations, and fewer still have assessed the role of gene flow in this process.…”
Section: (A) Consequences For Neutral Genetic Variationmentioning
confidence: 99%